Investigating the impact of the mid-season winter break on technical performance levels across European football - Does a break in play affect team momentum? - Jamil, M.; McErlain-Naylor, S. A.; Beato, M. (International Journal of Performance Analysis in Sport, 2020)
Using game-level data, this study examines what impact the mid-season winter break in football fixtures has on technical performance across European football leagues. Thirty-eight technical measures pertaining to the actions of passing and shooting are assessed for 3494 team match observations from the German Bundesliga, Spanish La Liga, French Ligue 1 and English Premier League across 5 seasons from 2013/14 to 2017/18. Kruskal-Wallis tests were conducted to investigate the differences between three groups: PREPRE (4-6 fixtures prior to the break); PRE (1-3 fixtures prior to the break); and POST (1-3 fixtures after the break). Shooting performance declined significantly post winter break in the German Bundesliga (13/21 metrics) which had an average break of 32 days. Passing performance deteriorated significantly in the French Ligue 1 (4/17 metrics) which had an average break of 19 days. The Spanish La Liga had a 13-day break on average and remained unaffected as did the English Premier League which had no mid-season break. Evidence suggests that a mid-season winter break of less than 13 days will not affect technical performance levels but breaks that last longer can act as a catalyst that halt momentum and cause performances to deteriorate.